1
$\begingroup$

Consider an Ito process $dS_t = f(t,S_t) dt + g(t,S_t)dW_t $

What is the reason that we can compute the variance as: $\sqrt{VaR(S_t)} = \frac{(dS_t)^2}{dt}$

$\endgroup$
2
$\begingroup$

Because instantaneous variance can be written as follows:

$V \left[ dS_t\right]=E\left[ \left( dS_t -E\left[dS_t\right] \right)^2\right]$

$V \left[ dS_t\right]=E\left[ \left( dS_t -f \, dt \right)^2\right]$

$V \left[ dS_t\right]=E\left[ \left( g \, dW_t \right)^2\right]=g^2dt$

Which is the same thing as:

$V \left[ dS_t\right]=E\left[ dS_t dS_t\right]=g^2dt$

Where I used the familiar drill $dtdt=0,dtdW=0, \text{ and } dWdW=dt$.

$\endgroup$
  • $\begingroup$ $E\left[ \left( g \, dW_t \right)^2\right]=g^2dt$. Why does this hold? thx $\endgroup$ – econmajorr Jun 15 at 15:25
  • 1
    $\begingroup$ This becomes $E\left[ g^2 dt \right]$ which is conditionally constant/known, so its expected value is its amazing self! $\endgroup$ – Magic is in the chain Jun 15 at 15:34
  • 1
    $\begingroup$ This is Ito's isometry: $\mathbb{E}[(\int g dW_t)^2] = \mathbb{E}[\int g^2 dt]$ $\endgroup$ – byouness Jun 17 at 19:45

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.